Answer:
(f ○ g)(x) = ![2^{x+1}](https://tex.z-dn.net/?f=2%5E%7Bx%2B1%7D)
Step-by-step explanation:
Substitute x = g(x) into f(x) , that is
(f ○ g)(x)
= f(g(x))
= f(x + 1)
= ![2^{x+1}](https://tex.z-dn.net/?f=2%5E%7Bx%2B1%7D)
Answer:
Is a scalene right triangle
Step-by-step explanation:
Classify the triangle
By the interior angles
Applying the Pythagoras Theorem
![c^{2}=a^{2} +b^{2}](https://tex.z-dn.net/?f=c%5E%7B2%7D%3Da%5E%7B2%7D%20%2Bb%5E%7B2%7D)
substitute the values
![5^{2}=3^{2} +4^{2}](https://tex.z-dn.net/?f=5%5E%7B2%7D%3D3%5E%7B2%7D%20%2B4%5E%7B2%7D)
------> is true
therefore
Is a right triangle
By the length sides
The triangle has three unequal sides
therefore
Is a scalene triangle
First, factor out h so the equation can be h(b+r)=25 then divide by b+r so h= 25/b+r